IMPLEMENTASIKEBIJAKAN RUANG PUBLIK TERPADURAMAH ANAK (RPTRA) DI RPTRA UTAMA CENGKARENG JAKARTA BARAT - Netti Herlina (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2018)
AbstractThis research was aimed to analyzed how the implementation of integrated children friendly public area in, Cengkareng, West Jakarta. Researcher used the implementation theory from Merilee S. Grindle which consist of two variables, that was content of policy (Interest Affected, Type of Benefits, Extent of Change Envision, Site of Decision Making, Program Implementer and Resources Committed) and context of policy (Power, Interest, and Strategy of Actor Involved, Institution and Regime Characteristi and Compliance and Responsiveness). The research method used is qualitative research. While the way data collection is done by library study, field observation and interview to informants that have been predetermined.Based on this research, the implementation of the integrated public friendly children area for the fulfillment of children’s right s to the environment has been going well.